Universal Design for Learning. A systematic review of its role in Teacher Education. - Sara De la Fuente-González; David Menéndez Álvarez-Hevia; Alejandro Rodríguez-Martín (Alteridad : Revista de Educación)
Universal Design for Learning (UDL) is a developing educational approach that aims to improve learning for all students without having to make significant modifications to the curriculum. This concept has been progressively incorporated into pedagogical debates and education regulations. Along this line, some publications have illustrated the efficacy of UDL in terms of access, participation, and commitment to learning processes, especially in the case of students with disabilities. This paper provides a systematic review of relevant academic literature that enhances our understanding of how UDL was integrated into teacher education processes by identifying three different forms of conceptualizing UDL. For this purpose, 88 articles were included that addressed the incorporation of Universal Design for Learning into initial and in-service teacher education processes. The results point to a dominant approach grounded on a problematic association of UDL with students with disabilities or learning difficulties. This narrow view restricts how teachers apply inclusive practices in classrooms, calling for a broader and more comprehensive interpretation of UDL. The study contributes to fostering discussions about Universal Design for Learning (UDL) as a whole, including the dominant perspective projected in how it is understood and applied in teacher education and classrooms. It envisions new, more inclusive scenarios for the development of educational approaches that support all learners, fostering a truly inclusive learning environment.